A method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts

By designing and preparing the connection layer of a three-dimensional silicon carbide nanowire network and a Ti3SiC2 layered structure, the connection temperature is reduced by using the self-propagation reaction, the problem of insufficient connection strength of the special-shaped structural parts of the fiber-reinforced ceramic matrix composite material is solved, high-strength connection is achieved and the problem of nano reinforced body content and distribution is overcome.

CN118125853BActive Publication Date: 2025-04-11SHANDONG YINUO RONGSHEN COMPOSITE MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410266560.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2025-04-11
Estimated Expiration
2044-03-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high-strength connection of fiber-reinforced ceramic matrix composite special-shaped structural parts or non-planar structural parts, especially under pressure-free connection conditions, the connection strength is low and it is difficult to meet the needs of engineering applications.

Method used

The nanocomposite connecting layer was prepared through sol-gel reaction and high-temperature carbonization process using a three-dimensional silicon carbide nanowire network and Ti3SiC2 with a unique nanolayer structure as the reinforcement and matrix of the connecting layer, and the nanocomposite connecting layer was prepared by the sol-gel reaction and high-temperature carbonization process, and the connection temperature was reduced by the self-propagation reaction of Ti-Si-C.

Benefits of technology

High-strength connection of fiber-reinforced ceramic matrix composite special-shaped structural parts is realized, with the connection strength up to 21.41MPa, which is several times higher than the prior art 4.71~6.87MPa, which overcomes the problem of introducing high content of nano reinforced bodies and improves the major disadvantages of traditional ceramic brittleness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118125853B_ABST
    Figure CN118125853B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for connecting fiber-reinforced ceramic-based composite material special-shaped structural parts, and relates to the technical field of composite materials. On the one hand, the present invention overcomes the agglomeration problem that is easy to occur when nano-scale reinforcements are directly added, and on the other hand, the content of nano-reinforcements in the connecting layer can be significantly increased, and finally the connection strength is significantly improved. Layered ceramics (such as Ti3SiC2, etc.) have a hexagonal crystal structure and have the characteristics of both ceramics and metals, such as high modulus, high fracture toughness, good thermal shock resistance, etc. As a connecting layer material, it can improve the disadvantage of large brittleness of traditional ceramics to a certain extent. At the same time, the self-propagating reaction of the Ti‑Si‑C system at high temperature helps to reduce the connection temperature, and the thickness of the Ti3SiC2 layer generated in situ is in the nanometer range. Its unique valence bond combination and nano-scale lamellar structure can cause plastic deformation similar to that of metals, which is of great significance to improving the brittleness of the joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a method for connecting fiber-reinforced ceramic-based composite material special-shaped structural parts. Background Art

[0002] In high-tech fields such as aerospace, fiber-reinforced ceramic matrix composites (such as carbon / carbon composites, carbon / silicon carbide composites, silicon carbide / silicon carbide composites) as a new type of high-temperature materials have been successfully applied to missile nose cones, wing leading edges, high-temperature fasteners, aircraft brake discs, etc. However, in the further development of large-sized and complex-shaped components, there are difficulties such as the difficulty of one-time weaving of complex preforms, the limitation of component size by densification equipment, and the limitation of component processing by fiber brittleness. Connecting smaller-sized composite materials to achieve the forming of large-sized and complex-shaped components is an effective means to solve these problems.

[0003] Depending on whether pressure is loaded during the connection process, the connection process can be divided into pressure connection and pressureless connection. At present, the connection methods suitable for high-temperature structural materials, such as diffusion connection, are mostly pressure connections. This method is difficult to achieve reliable connection of special-shaped structural parts or non-planar structural parts. Literature 1 "Fu Qiangang, Wang Le, Zhao Fengling, et al. A method for pressureless connection between C / C composite materials [P]. Shaanxi Province: CN106747553B, 2019-12-27" proposed a method of using the active components in the connection layer to react with the parent material under high temperature conditions to produce in-situ bonding, successfully realizing the pressureless connection of carbon / carbon composite materials, but the connection strength is low, only 4.71~6.87MPa, which is difficult to meet the needs of engineering applications.

[0004] Practice has proved that by combining two or more single materials with different physical and chemical properties through a certain process, the performance of the resulting composite material in certain aspects (such as mechanical properties, etc.) can be significantly better than that of a single material. The reinforcement is a crucial component in the structure of the composite material. The characteristics of the composite reinforcement and its uniform dispersion in the matrix determine the comprehensive performance of the composite material to a certain extent. Studies have shown that the toughening and strengthening effect of the reinforcement on the matrix is ​​not only closely related to the shape and content of the reinforcement (Document 2: Zhang Yang, Li Feilong, Chen Xiaoyang, etc. A multi-element multi-scale hybrid reinforced magnesium-lithium based composite material and its preparation method [P]. Jiangsu Province: CN110343921B, 2021-07-02), but also greatly limited by the dispersion of the reinforcement in the matrix (Document 3: Li Wei, Song Qiang, Qiang Qi, etc. A core-shell structure carbon nanotube reinforced carbon / carbon composite material and its preparation method [P]. Shaanxi Province: CN113480321B, 2022-09-13). When the content is the same, the better the dispersion of the reinforcement in the matrix, the better the reinforcement effect; when the degree of dispersion is equivalent, the higher the content of the reinforcement in the matrix, the better the reinforcement effect.

[0005] At present, there are two main ways to introduce nano-reinforcements into composite materials: one is direct addition, and the other is in-situ self-generation. When adding directly, the agglomeration problem of conventional zero-dimensional, one-dimensional and two-dimensional nano-reinforcements restricts the content of reinforcements in the composite structure; when in-situ self-generation, the content of nano-reinforcements is generally low. The above two points greatly limit the improvement of the reinforcement coefficient of composite materials. Summary of the invention

[0006] The present invention provides a low-temperature connection method suitable for fiber-reinforced ceramic matrix composite material special-shaped structural parts or non-planar structural parts, which is used to solve the problem that diffusion connection in the prior art is difficult to use for connection of special-shaped parts or special-shaped surfaces. In addition, compared with the conventional pressureless connection in the prior art, the method proposed by the present invention can increase the connection strength by more than 4 times.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions:

[0008] A method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts, comprising the following steps:

[0009] S1. Pre-treating the fiber-reinforced ceramic matrix composite material special-shaped structural parts to obtain a base material to be connected with a rough or porous surface and a complete interior. The pre-treating method is selected from laser etching or mechanical processing according to the type of material;

[0010] S2. Preparation of three-dimensional silicon carbide nanowire networks with a thickness of 0.1-10 mm and a density of 0-0.26 g / cm 3The three-dimensional carbon felt is used as the skeleton, siloxane is used as the silicon source and carbon source, and polysiloxane dry gel is obtained in the pores of the carbon felt through a sol-gel reaction. The gel curing temperature is 50-200°C, and the curing time is 2-48h. Then, a high-temperature carbonization process is combined to obtain a silicon carbide nanowire network. The carbonization temperature is 1300-1700°C, and the carbonization time is 0.1-24h. Then, the carbon felt template is removed by high-temperature oxidation at a temperature of 500-1000°C to obtain a three-dimensional nanonetwork.

[0011] S3, prepare titanium-silicon-carbon connecting layer powder, with an atomic ratio of 40-60% high-purity titanium, 10-30% high-purity silicon and 20-40% high-purity graphite powder as titanium source, silicon source and carbon source respectively, and 0-10% silicon carbide powder as an additive, use an agate ball mill at a speed of 100-450r / min for 0.1-12h to obtain a uniformly mixed connecting layer powder;

[0012] S4, prepare the joint under high temperature and pressureless conditions, ultrasonically clean and dry the pretreated mother materials to be connected, place the three-dimensional silicon carbide nanowire network obtained in S2 between the mother materials to be connected and tighten, place the connecting layer powder obtained in S3 in anhydrous ethanol at a content of 0.1~5g / mL, ultrasonicate for 1~30min to obtain a uniformly dispersed suspension, and drip the suspension into the three-dimensional silicon carbide nanowire network between the mother materials to be connected, with a dripping amount of 0.01~10mL / mm 2 , place the assembled base material to be connected in a high temperature furnace, heat it to 800~1300℃ at a rate of 5-20℃ / min, keep it warm for 0.1~1h, and then cool it to room temperature at a rate of 1~50℃ / min, with high vacuum or argon protection throughout the process.

[0013] Preferably, the high-purity titanium, high-purity silicon, high-purity graphite powder and silicon carbide powder are all analytically pure and have a particle size of -500 mesh.

[0014] The advantages of the present invention are:

[0015] The present invention proposes a method for connecting special-shaped structural parts of fiber-reinforced ceramic-based composite materials. The method adopts a pressure-free connection method to achieve high-strength connection of special-shaped structural parts or non-planar structural parts. By designing and preparing a three-dimensional network-like nanostructure, the difficulty of introducing a high content of nano-reinforcement is overcome, and the uniform distribution of nano-level reinforcement fibers in the connection layer is achieved. The three-dimensional silicon carbide nanowire network and Ti3SiC2 with a unique nano-layered structure are used as the reinforcement and matrix of the connection layer respectively, and the self-propagating reaction of Ti-Si-C is used to effectively reduce the connection temperature, avoid damage to the mechanical properties of the matrix material due to the high temperature of the connection process, and at the same time realize the densification process of the three-dimensional silicon carbide nanowire network to obtain a nano-composite connection layer.

[0016] The carbon / carbon composite material connector connected by the nanocomposite connecting layer prepared in the present invention has a connection strength of up to 21.41 MPa, which is several times higher than the 4.71-6.87 MPa obtained in the first document and has a higher connection strength.

[0017] The invention proposes a method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts, designs and constructs a three-dimensional silicon carbide nanowire network reinforced layered ceramic connection layer, and its advantage is that the design and implementation of the nano network can simultaneously improve the content and distribution uniformity of the nano reinforcement in the connection layer. On the one hand, this method overcomes the agglomeration problem that is easy to occur when the nano-level reinforcement is directly added, and on the other hand, it can significantly increase the content of the nano reinforcement in the connection layer, and finally significantly improve the connection strength. The layered ceramic (such as Ti3SiC2, etc.) has a hexagonal crystal structure and has the characteristics of both ceramics and metals, such as high modulus, high fracture toughness, good thermal shock resistance, etc. As a connection layer material, it can improve the disadvantage of large brittleness of traditional ceramics to a certain extent. At the same time, the self-propagating reaction of the Ti-Si-C system at high temperature helps to reduce the connection temperature, and the thickness of the Ti3SiC2 layer generated in situ is in the nanometer range. Its unique valence bond combination and nano-level lamellar structure can cause plastic deformation similar to metal, which is of great significance to improving the brittleness of the joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a process flow chart of the present invention.

[0019] Figure 2 This is a macroscopic photograph of the three-dimensional silicon carbide nanowire network prepared by the present invention.

[0020] Figure 3 This is a microscopic photograph of the three-dimensional silicon carbide nanowire network prepared by the present invention.

[0021] Figure 4 It is a cross-sectional microscopic photograph of the joint prepared by the present invention. DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0023] A method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts, comprising the following steps:

[0024] S1. Pre-treating the carbon / silicon carbide composite material to be connected by mechanical method to obtain a base material to be connected with a rough surface and a complete interior;

[0025] S2. Preparation of three-dimensional silicon carbide nanowire network with a thickness of 0.5 mm and a density of 0.1 g / cm 3The three-dimensional carbon felt is used as the skeleton, and siloxane is used as the silicon source and carbon source. The polysiloxane dry gel is obtained in the pores of the three-dimensional carbon felt through a sol-gel reaction. The gel curing temperature is 80°C and the curing time is 4h. Combined with the high-temperature carbonization process, a three-dimensional silicon carbide nanowire network is obtained. The carbonization temperature is 1500°C and the carbonization time is 1h. Then the three-dimensional carbon felt template is removed by high-temperature oxidation at a temperature of 800°C to obtain a three-dimensional silicon carbide nanowire network.

[0026] S3, prepare titanium-silicon-carbon connecting layer powder, with an atomic ratio of 50% high-purity titanium, 18% high-purity silicon and 30% high-purity graphite powder as titanium source, silicon source and carbon source respectively, and 2% silicon carbide as an additive, use an agate ball mill at a speed of 300r / min for 1h to obtain a uniformly mixed connecting layer powder;

[0027] S4. Prepare the joint under high temperature and pressure-free conditions. The specific steps are as follows:

[0028] Step 1: ultrasonically clean and dry the pre-treated base material to be connected;

[0029] Step 2: placing the nano-reinforcement network obtained in S2 between the base materials to be connected and fastening them;

[0030] Step 3: The connecting layer powder obtained in S3 is placed in anhydrous ethanol at a content of 0.5 g / mL, and ultrasonicated for 10 minutes to obtain a uniformly dispersed suspension;

[0031] Step 4: Drop the suspension containing the powder at the airport into the three-dimensional silicon carbide nanowire network between the base materials to be connected, with a drop volume of 0.5mL / mm 2 ;

[0032] Step 5: Place the assembled base material to be connected in a high-temperature furnace, heat it to 1200°C at a rate of 10°C / min, keep it warm for 0.5h, then cool it to room temperature at a rate of 10°C / min, and maintain high vacuum throughout the process (vacuum is about 1.0×10-3Pa).

[0033] After taking out the sample, it was processed into a size of 10×8×8 and its connection strength was tested by the compression shear method. The test results showed that the average shear strength of the prepared joint was 21.41 MPa, and the average loading speed of the press during the test was 0.2 mm / min.

[0034] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts, characterized in that: The following steps are involved: S1. Pre-treating the fiber-reinforced ceramic matrix composite material special-shaped structural parts to obtain a base material to be connected with a rough or porous surface and a complete interior. The pre-treating method is selected from laser etching or mechanical processing according to the type of material; S2. Preparation of three-dimensional silicon carbide nanowire networks with a thickness of 0.1-10 mm and a density of 0-0.26 g / cm 3 The three-dimensional carbon felt is used as the skeleton, siloxane is used as the silicon source and carbon source, and polysiloxane dry gel is obtained in the pores of the three-dimensional carbon felt through a sol-gel reaction. The gel curing temperature is 50-200°C, and the curing time is 2-48h. Then, the three-dimensional carbon felt is removed by high-temperature oxidation at a temperature of 500-1000°C to obtain a three-dimensional silicon carbide nanowire network. S3, prepare titanium-silicon-carbon connecting layer powder, use an agate ball mill to high-speed ball mill 40-60% high-purity titanium, 10-30% high-purity silicon, 20-40% high-purity graphite powder and 0-10% silicon carbide powder at a speed of 100-450r / min for 0.1-12h to obtain a uniformly mixed connecting layer powder; S4, prepare the joint under high temperature and pressureless conditions, ultrasonically clean and dry the pretreated mother materials to be connected, place the three-dimensional silicon carbide nanowire network obtained in S2 between the mother materials to be connected and tighten, place the connecting layer powder obtained in S3 in anhydrous ethanol at a content of 0.1~5g / mL, ultrasonicate for 1~30min to obtain a uniformly dispersed suspension, and drip the suspension into the three-dimensional silicon carbide nanowire network between the mother materials to be connected, with a dripping amount of 0.01~10mL / mm 2 , place the assembled base material to be connected in a high temperature furnace, heat it to 800~1300℃ at a rate of 5-20℃ / min, keep it warm for 0.1~1h, and then cool it to room temperature at a rate of 1~50℃ / min, with high vacuum or argon protection throughout the process.

2. The method for connecting fiber-reinforced ceramic matrix composite material special-shaped structural parts according to claim 1, characterized in that: The high-purity titanium, high-purity silicon, high-purity graphite powder and silicon carbide powder are all analytically pure and have a particle size of 500 meshes.

Citation Information

Patent Citations

  • Pressure-free connection method of C / C composite materials

    CN106747553A

  • Multi-element multi-size mixed enhanced magnesium lithium-based composite material and preparation method thereof

    CN110343921A

  • Core-shell structure carbon nanotube reinforced carbon / carbon composite material and preparation method thereof

    CN113480321A

  • Porous ceramic connecting method

    CN105272369A

  • Method for improving connection performance of carbon / carbon composite material and lithium aluminum silicate glass ceramic

    CN106866166A